Analysis of students' 21st century skills in Biology class X at SMAN 12 Padang - Maulidia Fitri; Ade Dewi Maharani; Erismar Amri (Quagga: Jurnal Pendidikan dan Biologi, 2024)
This research aims to determine the 21st century skills abilities of class X students in Biology learning at SMAN 12 Padang. This type of research is descriptive research. The population in this study were all students in class XI.IPA at SMAN 12 Padang, totaling 179 students. The sample taken was 45 students using random sampling techniques. The instruments used are questions to measure critical thinking skills and observation sheets to measure creative thinking skills, collaboration skills and communication skills. The questions used in this research are questions that have been tested for validity and reliability. The results of research conducted at SMAN 12 Padang on class XI odd semester students in the 2023/2024 academic year, namely critical thinking skills 44 with sufficient criteria, creative thinking skills 65 with high criteria, collaboration skills 76 with high criteria, and communication skills 69 with high criteria. So it can be concluded that students' 21st century skills in biology learning at SMAN 12 Padang meet high criteria.